Local Retailers Response to Retail Internationalisation:Malaysia Perspective - Wong, Poh Ling (2005)
This paper explores the entirety of grocery retail internationalisation, and the happening in the Malaysian Grocery Retail. The results of a field study suggest that local retailers were generally optimistic about the industry in the next ten years, and the examination on their strategic behaviour in the face of grocery retail internationalisation suggests that local retailers have learned and understood the need for modernised strategies in their strategic posture as well as their competitive practices. Their strategic posture were discussed in four categories; `neutralising competitors reaction’, `establishing competitive advantage’, `redefining markets’, and `changing ownership’. Whilst their competitive practices found five distinctive patterns; `retail presentation and image’, `low price with intensive promotion’, `house brand’, `service’ and `product quality and uniqueness’.